Biomechanical analysis of elite female rugby place kickers - Atack, A. C.; Bezodis, N. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to investigate rugby place kicking technique of elite female players. Five International-level female place kickers took at least five maximum range place kicks, and their technique was analysed using 3D motion capture. In comparison to successful male kickers, females achieved slower kicking foot and ball velocities and shorter maximum kicking distances. Reduced extension of the support leg hip and knee joints, combined with slower centre of mass deceleration, meant that females appeared to transfer less momentum from their approach to the ball, thus, requiring them to perform more positive work at their kicking hip. A faster approach to the ball and more pronounced support leg extension may enable females to achieve greater place kicking distances.